Determinants of Social and Emotional Loneliness in a Nationally Representative Sample of US Adults (European Journal of Behavioral Sciences, 2022)
Loneliness is a pervasive global health concern and a plethora of studies have linked it to high mortality and morbidity and psychological problems, such as depression, suicidal ideation, and anxiety. Furthermore, growing evidence suggests that loneliness is a bi-dimensional construct made up of two related but distinct categories; social and emotional loneliness. In order to inform future intervention strategies and aid clinicians in tackling this growing ‘epidemic’, data collected by the Growth from Knowledge group (GFK) from a nationally representative sample of adults residing in the US (n=1,839) was used to evaluate the relationship between both subtypes and overall loneliness with a multitude of demographics. Results suggest that being female, younger aged adults, low income, those who are not married nor cohabiting, unemployed, have a high school degree or less, and identify as white are more likely to report feeling emotionally lonely. Younger adults, low income, and those with a high school degree were associated with social loneliness and young adults, low income, those who are not married nor cohabiting, and living in a metro area was significantly linked to total loneliness. These results support the distinction between the loneliness subtypes and it is recommended that researchers and clinicians acknowledge this distinction when developing future prevention and intervention strategies.